Договор ACTA - защита интеллектуальной собственности или попытка ограничения свободы в интернете? - Żebrowski, Paweł (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to analyse the Acta Agreement in the context of the question whether it is a form of protection intellectual property rights or an attempt to limit Internet freedom. The author presents the Acta Agreement content, concerns about it, social reaction and European Union standing.